Biopolitical governance : race, gender and economy - Richter, Hannah, 1990- (Global political economies of gender and sexuality., 2018)
This collection brings together contributions from both established scholars and researchers working at the forefront of biopolitical theory, gendered and sexualised governance and the politics of race and migration.